Canada. Significant achievements 2010 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Canada during 2010 are identified, with respect to the needs and interests of the country, strengthening issues such as sustainability, public policies, food safety, agribusiness, financing, trade, composting, biogas, waste management. , food production and emergency management, prevention, preparedness and recovery.